Investigação teórica da quimisssorção do ânion metanossulfonato em eletrodos de platina (111) e (100) via método semi-empírico - Folkuenig, Engelbert de Souza (2010)
Several electrochemical processes, such as electrocatalysis of organic substrates, make use of mediators. One of the mediators is the most commonly used anion methanesulfonate, CH3SO3, which has several advantages for such use, and chemical stability considered one of them. However, experimental studies indicate the possibility of this compound suffer the adsorption and decomposition on platinum electrodes. To get an understanding at the molecular level these processes, computer simulations were performed with the aid of the semi-empirical PM6. The cluster approach was used in the modeling of platinum surfaces with crystallographic orientations (111) and (100). The symmetries of most stable adsorption calculated for the anion in these areas correspond to the experimental data: C3V symmetry in (111) surface and C1 in (100) surface. To simulate the potential applied to the electrode, external electric fields with a positive sign and perpendicular to the surface of the clusters were applied. Changes in the lengths and angles of bonds adsorbed anion, as well as its values of dipole moment were observed. The infrared spectra of the systems anion-clusters were calculated and the values for the Stark tunning rate (Δstark) of mode δs CH3 were compared with the experimental value. Both for the free anion and for systems where the anion is adsorbed, it was found that the values of Δstark assumed negative values (indicating that the frequency of the vibrational mode δs CH3 diminished with increasing external eletric field), opposite to the experimental positive value (frequency mode δs CH3 increases with the increase in potential). Only with the addition of water molecules in the systems studied, in order to simulate the aqueous solvent is that the values of Δstark started to assume a positive value. The comparison showed the importance of the presence of water molecules in the simulation of an electrochemical system and prompted a detailed analysis of the frontier orbitals involved in this process. It was found that the dipole-dipole coupling between water molecules and the adsorbed anion is responsible for the Stark effect, while the electrostatic interactions between various molecules adsorbed anion affect the intensity of the absorption band mode δs CH3 in the spectra calculated. In (100) surfaces, the joint action of external field and water molecules, lead the anion molecule to adopt the adsorption geometries more inclined to systems without water molecules, indicating that this may be an important factor in explaining the greater reactivity of the anion on the surface.